Species Delimitation of the Eisenia nordenskioldi Complex (Oligochaeta, Lumbricidae) Using Transcriptomic Data - Shekhovtsov, Sergei V.; Shipova, Aleksandra A.; Poluboyarova, Tatiana V.; Vasiliev, Gennady V.; Golovanova, Elena V.; Geraskina, Anna P.; Bulakhova, Nina A.; Szederjesi, Tímea; Peltek, Sergei E. (Frontiers in Genetics, 2020)
Eisenia nordenskioldi (Eisen, 1879) is the only autochthonous Siberian earthworm with a large distribution that ranges from tundra to steppe and broadleaved forests. This species has very high morphological, ecological, karyological, and genetic diversity, so it was proposed that E. nordenskioldi should be split into several species. However, the phylogeny of the complex was unclear due to the low resolution of the methods used and the high diversity that should have been taken into account. We investigated this question by (1) studying the diversity of the COI gene of E. nordenskioldi throughout its range and (2) sequencing transcriptomes of different genetic lineages to infer its phylogeny. We found that E. nordenskioldi is monophyletic and is split into two clades. The first one includes the pigmented genetic lineages widespread in the northern and western parts of the distribution, and the second one originating from the southern and southeastern part of the species’ range and representing both pigmented and nonpigmented forms. We propose to split the E. nordenskioldi complex into two species, E. nordenskioldi and Eisenia sp. 1 (aff. E. nordenskioldi), corresponding to these two clades. The currently recognized nonpigmented subspecies E. n. pallida will be abolished as a polyphyletic and thus a non-natural taxon, while Eisenia sp. 1 will be expanded to include several lineages earlier recognized as E. n. nordenskioldi and E. n. pallida.